Gingival crevicular fluid alkaline phosphatase as a potential diagnostic marker of periodontal disease - Sheetal Sanikop; Suvarna Patil; Pallavi Agrawal (Wolters Kluwer Medknow Publications, 2012)
Background: Alkaline phosphatase (ALP) enzyme is involved in the destruction of the human periodontium. The present study was conducted to determine the presence and levels of ALP activity in gingival crevicular fluid (GCF) in periodontal health, gingivitis, and chronic periodontitis. Materials and Methods: GCF samples were collected from 45 sites which were divided into three equal groups of healthy samples and gingivitis and chronic periodontitis samples. Various clinical parameters were evaluated and the levels of ALP were estimated using a semi-autoanalyzer. Analysis of variance was employed to compare the ALP levels in different groups. Pearson's correlation coefficient was utilized to find the correlation between ALP levels and various clinical parameters. Results: Difference in the mean ALP levels between healthy and gingivitis groups was found to be nonsignificant (P>0.05) and that between the chronic periodontitis group and healthy as well as gingivitis groups was found to be highly significant (P<0.001). Significant correlations existed between ALP levels and gingival index, probing depths, as well as clinical attachment levels. Conclusion: The finding of the present study confirms the relationship between ALP level and periodontal disease, thus indicating that GCF ALP levels can be used as potential biochemical markers for the detection and progression of periodontal disease.